Foucault’s “Marxist moment”: The Punitive Society in perspective - Chamorro, Emmanuel (Logos. Anales del Seminario de Metafísica, 2023)
This paper analyzes the course that Michel Foucault taught in 1973 at the Collège de France under the title La société punitive. Through a conceptual and contextual reconstruction of the course we will try to clarify its debt to the Marxist perspective. This link leads to an analysis that attends to the specificity of power relations, but - in consonance with the approach of many of the radical and countercultural movements of its time - connects them to the development of capitalist society. Critique of political economy, genealogy of morality and analysis of power compose the three axes from which Foucault proposes a sensitively different history of disciplinary society than that which he will propose only two years later in Discipline and Punish. In this way, the 1973 course shows the Marxist roots of the research that Foucault developed in the first half of the 1970s and which rejection will have a strong impact on his work on government and the care of the self.